Trientine tetrahydrochloride versus penicillamine for maintenance therapy in Wilson disease (CHELATE): a randomised, open-label, non-inferiority, phase 3 trial. (December 2022) - Schilsky, Michael L; Czlonkowska, Anna; Zuin, Massimo; Cassiman, David; Twardowschy, Carlos; Poujois, Aurelia; Gondim, Francisco de Assis A; Denk, Gerald; Cury, Rubens G; Ott, Peter; Moore, Joanna; Ala, Aftab; et al.
Summary: Background: Wilson disease is an inherited disorder of copper transport. Whereas penicillamine is used therapeutically to re-establish copper balance, trientine is indicated for patients with penicillamine intolerance. We aimed to compare penicillamine with trientine tetrahydrochloride (TETA4) for maintenance therapy in patients with Wilson disease. Methods: We conducted a randomised, open-label, non-inferiority, phase 3 trial at 15 health-care centres across nine countries (patients were recruited from 13 of these health-care centres across Brazil, Europe, and the USA). We enrolled patients aged 18–75 years with stable Wilson disease who were treated for at least 1 year with penicillamine. Patients entered a 12-week period to determine stability through clinical assessment by site investigators and predefined thresholds for serum non-caeruloplasmin-bound copper (NCC; by an exchangeable copper assay; 25–150 μg/L), 24 h urinary copper excretion (100–900 μg/24 h), and alanine aminotransferase (ALT; <2 × upper limit of normal). Stable patients were randomly assigned (1:1) to continue receiving the maintenance twice daily dose of oral penicillamine or switched mg-for-mg to oral TETA4 centrally with a web-based system using minimisation. The primary endpoint, assessed 24 weeks after randomisation, was NCC by speciation assay. The non-inferiority margin of mean difference in NCC by speciation assay was –50 μg/L, as estimated by a general linear model for repeated visits, adjusted for baseline values. Further data on safety and efficacy were collected during a 24-week extension period. Data were analysed using an intention-to-treat approach. Safety was assessed in all patients who received at least one dose of study treatment. This study is registered with ClinicalTrials.gov, NCT03539952 (active, not recruiting). Findings: Between June 4, 2018, and March 10, 2020, 77 patients were screened. 53 patients were randomly assigned (27 to the penicillamine group and 26 to the TETA4 group). After 24 weeks, the mean difference in serum NCC by speciation assay between the penicillamine group and TETA4 group was –9·1 μg/L (95% CI –24·2 to 6·1), with the lower limit of the 95% CI within the defined non-inferiority margin. At 24 weeks, urinary copper excretion was lower with TETA4 than with penicillamine (mean difference 237·5 μg/24 h (99% CI 115·6 to 359·4). At 48 weeks, TETA4 remained non-inferior to penicillamine in terms of NCC by speciation assay (mean difference NCC −15·5 μg/L [95% CI –34·5 to 3·6]). Urinary copper excretion at 48 weeks remained in the expected range for well treated patients in both study groups, and the mean difference (124·8 μg/24 h [99% CI –37·6 to 287·1]) was not significantly different. At 24 weeks and 48 weeks, masked clinical adjudication of stability assessed by three independent clinicians confirmed clinical stability (100%) of all participants, in agreement with the stability seen with the NCC by speciation assay. There were no notable changes in either the Clinical Global Impression of Change or Unified Wilson Disease Rating Scale (neurological assessment) from baseline (pre-randomisation) at weeks 24 and 48. The mean change in serum total copper from baseline to 24 weeks was 17·6 μg/L (99% CI –9·5 to 44·7) with penicillamine and –6·3 μg/L (–34·7 to 22·1) with TETA4, and the mean change in serum total caeruloplasmin from baseline to 24 weeks was 1·8 mg/L (–19·2 to 22·8) with penicillamine and –2·2 mg/L (–6·1 to 1·7) with TETA4. All liver enzymes were similar at 24 weeks and 48 weeks, with the exception of elevated ALT concentration at 48 weeks for patients in the TETA4 group. Penicillamine was associated with three post-randomisation serious adverse events (leukopenia, cholangiocarcinoma, and hepatocellular cancer); none were reported for TETA4. The most common treatment-emergent adverse events were headache for penicillamine (five [19%] of 27 patients vs two [8%] of 26) and abdominal pain for TETA4 (one [4%] vs four [15%]); all treatment-emergent adverse events resolved and were mild to moderate. One patient developed a rash with TETA4 that resolved on discontinuation of therapy. Interpretation: The efficacy of TETA4 as oral maintenance therapy was non-inferior to penicillamine and well tolerated in adults with Wilson disease. Funding: Orphalan.